A multicenter, phase 1, dose escalation clinical trial (G-FORCE-1) of XRT, RRx-001 and temozolomide followed by temozolomide +/- RRx-001 in newly diagnosed glioblastoma - Fine, Howard; Reid, Tony; Caroen, Scott; Oronsky, Bryan; Abrouk, Nacer; Butowski, Nicholas (Frontiers in Oncology, 2023)
Introduction The current standard of care for newly diagnosed glioblastoma (GBM) is maximum surgical resection followed by concurrent treatment with temozolomide (TMZ) and radiotherapy (RT) and then six to twelve cycles of maintenance TMZ. RRx-001, an NLRP3 inhibitor and nitric oxide (NO) donor with chemoradiosensitizing, vascular normalizing and macrophage repolarizing properties, is currently in a Phase III trial for small cell lung cancer (SCLC). The purpose of this non-randomized trial was to establish the safety and look for a signal of clinical activity of RRx-001 as an add-on to RT and TMZ in patients with newly diagnosed glioblastoma. Methods In this non-randomized, open-label, two part trial called G-FORCE-1 (NCT02871843), the first four cohorts of adult patients with histologically confirmed high grade gliomas received fractionated radiotherapy (60 Gy in 30 fractions over 6 weeks), daily 75 mg/m2 temozolomide and escalating doses of once weekly RRx-001 from 0.5 mg to 4 mg according to a 3+3 design followed by a 6 week no treatment interval and then standard maintenance TMZ (150 mg/m2 Cycle 1 and 200 mg/m2 in subsequent cycles) until disease progression. The second two cohorts of patients received fractionated radiotherapy (60 Gy in 30 fractions over 6 weeks), daily 75 mg/m2 temozolomide and once weekly RRx-001 4 mg followed by a 6 week no treatment interval and then two different maintenance schedules until disease progression according to the same 3+ 3 design: 1. 0.5 mg RRx-001 once weekly + 100 mg/m2 TMZ 5 days/week for up to 6 cycles of therapy; 2. 4 mg RRx-001 once weekly + 100 mg/m2 TMZ 5 days/week for up to 6 cycles of therapy The primary endpoint was the recommended dose/maximally tolerated dose of the combination of RRx-001, TMZ and RT. Secondary endpoints were overall survival, progression free survival, objective response rate, duration of response and clinical benefit response. Results A total of 16 newly diagnosed glioblastoma patients were enrolled. No dose limiting toxicities were observed and no MTD was reached. The recommended dose is 4 mg. After 24 months of follow up the median OS was 21.9 months (95% CI: 11.7 – NA). PFS median was 8 months (95% CI: 5 – NA). The overall response rate was 18.8% (3 PR out of 16) and the disease control rate was 68.8% (3 PR, 8 SD out of 16). Conclusions The addition of RRx-001 to TMZ and RT and to TMZ during maintenance was safe and well-tolerated and deserves further study.